Negative electrode binder, negative electrode plate and secondary battery

By introducing specific copolymer units into the negative electrode binder and optimizing their mass ratio, the problems of low peel strength and cycle life of the existing negative electrode binder coating are solved, and higher bonding forces and longer battery cycle life are achieved.

CN119662169AActive Publication Date: 2025-03-21SHENZHEN HAODYNE TECH CO LTD

Patent Information

Application Number
CN202510203387.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-21
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

The existing negative electrode binder has low coating peel strength and cycle life in thick electrode systems, which affects the performance of lithium-ion batteries.

Method used

A copolymer negative electrode binder is adopted, including acrylate units, vinyl aromatic units, acrylamide units, acrylate-polyol units and crosslinking units. By optimizing the mass ratio of these units, the electrolyte swelling and adhesion of the binder is improved.

Benefits of technology

The adhesion of the negative electrode active material layer is improved, the pole rebound and full-electric rebound are reduced, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a negative electrode binder, a negative plate and a secondary battery in order to solve the problems of low peeling strength and low cycle life of a coating of an existing negative electrode binder. The negative electrode binder comprises a copolymer, and the copolymer comprises an acrylate unit, a vinyl aromatic unit, an acrylamide unit, an acrylate-polyol unit and a crosslinking unit. According to the negative electrode binder provided by the invention, the negative electrode active material layer has relatively high binding power, low pole piece rebound and relatively small full-charge rebound, so that the long cycle life of the battery is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a negative electrode binder, a negative electrode sheet and a secondary battery. Background Art

[0002] Lithium-ion batteries have become the main power source of choice for modern portable electronic devices, electric vehicles and energy storage systems due to their advantages such as high energy density, long cycle life and low self-discharge rate. There are also higher requirements for their electrical properties including low-temperature cycle performance, rate performance and storage performance.

[0003] At present, technicians in this field have done a lot of work to improve the electrochemical performance of batteries, improve the working efficiency and reliability of lithium-ion batteries, and meet the needs of most application scenarios. At present, there have been studies to improve the low-temperature performance and rate performance of batteries by optimizing electrolyte formula, improving electrode materials, optimizing electrode structure, and improving binder composition. Among them, the negative electrode binder improves the adhesion between the negative electrode active layer and the negative electrode current collector, ensures the structural stability and conductivity of the negative electrode sheet, and reduces the probability of lithium dendrite precipitation, thereby improving the low-temperature cycle performance and rate performance of lithium-ion batteries.

[0004] Conventional negative electrode binders are mainly styrene-butadiene rubber (SBR), which is a polymer copolymerized from 1,3-butadiene and styrene. The SBR emulsion itself is a product of balanced hydrophilicity and hydrophobicity. On the one hand, it organically combines graphite through hydrophobicity, and on the other hand, it forms chemical bonds through condensation reaction between hydrophilic groups and oxides or hydroxyl groups on the surface of copper foil, providing adhesion between negative electrode active material particles and between active material layer and current collector. Its main advantages are stable performance in battery cells, moderate adhesion, low price and wide application. However, because its aqueous emulsion is a small molecule linear chain emulsion, it has good elasticity after film formation, resulting in a large degree of thickness rebound of the negative electrode sheet after rolling, and a large rebound when the battery cell is fully charged, affecting the cycle life of the battery cell; and the SBR binder has insufficient adhesion to the foil.

[0005] Therefore, how to improve the coating peeling strength and cycle life of thick electrode systems is an urgent problem to be solved. Summary of the invention

[0006] The present invention aims at the problems of low peeling strength and cycle life of the existing negative electrode binder coating, and provides a negative electrode binder, a negative electrode sheet and a secondary battery.

[0007] In order to solve the above technical problems, the present invention provides a negative electrode binder, which includes a copolymer, and the copolymer includes an acrylate unit, a vinyl aromatic unit, an acrylamide unit, an acrylate-polyol unit and a crosslinking unit.

[0008] Preferably, the mass ratio of the acrylate units, vinyl aromatic units, acrylamide units, acrylate-polyol units and cross-linked structural units is (30-70): (10-50): (5-30): (8-25): (0.5-2).

[0009] Preferably, the copolymer further comprises a cationic unit, which is a structural unit obtained by polymerization of a cationic monomer containing a double bond, and the cationic monomer comprises one or more of methacryloyloxyethyl dimethyl dodecyl ammonium bromide, methacryloyloxyethyl dimethyl hexadecyl ammonium bromide, methacryloyloxyethyl trimethyl ammonium bromide, methacryloyloxyethyl dimethyl butyl ammonium bromide, methacryloyloxyethyl dimethyl pentyl ammonium bromide, methacryloyloxyethyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium chloride and dimethyl diallyl ammonium chloride.

[0010] Preferably, the mass ratio of the acrylic acid ester unit to the cationic unit is (30-70): (5-30).

[0011] Preferably, the acrylate unit is a structural unit obtained by polymerization of acrylate monomers, and the acrylate monomers include one or more of methyl acrylate, ethyl acrylate, isobutyl acrylate, tert-butyl acrylate, butyl acrylate, 2-isooctyl acrylate, lauryl acrylate, octadecyl acrylate, methyl methacrylate, butyl methacrylate, phenyl methacrylate, and n-hexyl acrylate.

[0012] Preferably, the vinyl aromatic unit is a structural unit obtained by polymerization of a vinyl aromatic monomer, and the vinyl aromatic monomer includes one or more of styrene, β-methylstyrene, 4-methoxystyrene, and 2-methylstyrene.

[0013] Preferably, the acrylamide units are structural units obtained by polymerization of acrylamide monomers, and the acrylamide monomers include one or more of hydroxyethyl acrylamide, isobutoxymethyl acrylamide and diacetone acrylamide.

[0014] Preferably, the acrylate-polyol unit is a structural unit obtained by polymerization of acrylate-polyol monomers, and the acrylate-polyol monomers include one or more of poly(ethylene glycol) diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, and poly(propylene glycol) dimethacrylate; And / or, the cross-linking unit is a structural unit obtained by polymerization involving a cross-linking agent, and the cross-linking agent includes one or more of diethylene glycol dimethacrylate, ethylene glycol diacrylate, tetra(ethylene glycol) diacrylate, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol diacrylate, 1,6-hexanediol dimethacrylate, and pentaerythritol tetraacrylate.

[0015] In a second aspect, the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer is made of any of the negative electrode binders described above.

[0016] In a third aspect, the present application provides a secondary battery, comprising a positive electrode sheet, an electrolyte, and the negative electrode sheet as described above.

[0017] In the present application, the negative electrode binder introduces acrylate units, vinyl aromatic units, acrylamide units, acrylate-polyol units and cross-linking units, so that the negative electrode binder has an electrolyte mass swelling degree of 35% to 85%, and the negative electrode active material layer has a higher bonding force, a lower electrode rebound and a smaller full-charge rebound, thereby ensuring that the battery has a long cycle life. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0019] An embodiment of the present application provides a negative electrode binder, wherein the negative electrode binder includes a copolymer, wherein the copolymer includes an acrylate unit, a vinyl aromatic unit, an acrylamide unit, an acrylate-polyol unit, and a cross-linking unit.

[0020] The negative electrode binder of this embodiment introduces acrylate units, vinyl aromatic units, acrylamide units, acrylate-polyol units and cross-linking units, so that the negative electrode binder has an electrolyte mass swelling degree of 35% to 85%, and the negative electrode active material layer has a higher bonding force, low pole piece rebound and smaller full-charge rebound, ensuring that the battery has a long cycle life.

[0021] In some embodiments, the mass ratio of the acrylate units, vinyl aromatic units, acrylamide units, acrylate-polyol units and cross-linked structural units is (30-70): (10-50): (5-30): (8-25): (0.5-2). By optimizing the mass ratio of the acrylate units, vinyl aromatic units, acrylamide units, acrylate-polyol units and cross-linked units, the negative electrode binder has a moderate electrolyte mass swelling degree, and the negative electrode active material layer has a higher bonding force, a low pole piece rebound and a smaller full-charge rebound, ensuring that the battery has a long cycle life. The acrylate units are used to adjust the electrolyte swelling degree of the copolymer and provide bonding force with the active material and the foil. The vinyl aromatic units are mainly used to stabilize the structure of the copolymer and maintain a certain glass transition temperature, thereby improving the cracking problem during the pole piece processing. The polar functional group of the acrylamide unit is mainly used to further increase the bonding force with the active material and the foil. The cross-linked network structure formed by the acrylate-polyol units and the cross-linking agent is used to control the swelling degree of the copolymer in part and to control the rebound of the binder itself in another part, thereby effectively suppressing the rebound of the active coating.

[0022] If there are too many acrylate units, although the adhesion of the coating can be improved to a certain extent, acrylates have good affinity with the electrolyte, resulting in greater swelling of the binder, increasing the rebound of the fully charged battery cell, and the large rebound causes the negative electrode active material layer and the foil to partially fall off in the late cycle, resulting in a reduced cycle life. Fewer acrylate units will lead to lower swelling, a lower lithium ion migration rate, and reduced adhesion to the active material and the foil. If there are too many vinyl aromatic units and acrylamide units, the glass transition temperature of the binder will increase, and the electrode will easily crack during the processing and baking process, resulting in hard and brittle electrodes, rolling shedding and other problems. Too few units will lead to an unstable binder structure. Too many acrylate-polyol units will also lead to an increase in the glass transition temperature of the binder. Too few acrylate-polyol units cannot ensure that the binder has a certain degree of swelling and control the rebound of the binder itself.

[0023] Specifically, the mass ratio of acrylate units, vinyl aromatic units, acrylamide units, acrylate-polyol units and cross-linked structural units includes but is not limited to 30:50:30:25:2, 70:10:5:8:0.5, 50:30:20:15:1 or 40:20:20:15:1.

[0024] In a preferred embodiment, the mass ratio of acrylate units, vinyl aromatic units, acrylamide units, acrylate-polyol units and cross-linking structural units is (40-55): (20-35): (15-25): (13-20): (1-1.5).

[0025] In some embodiments, the copolymer further includes a cationic unit, which is a structural unit obtained by polymerization of a cationic monomer containing a double bond, and the cationic monomer includes one or more of methacryloyloxyethyl dimethyl dodecyl ammonium bromide, methacryloyloxyethyl dimethyl hexadecyl ammonium bromide, methacryloyloxyethyl trimethyl ammonium bromide, methacryloyloxyethyl dimethyl butyl ammonium bromide, methacryloyloxyethyl dimethyl pentyl ammonium bromide, methacryloyloxyethyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium chloride and dimethyl diallyl ammonium chloride.

[0026] By introducing cationic units into the binder to form a cationic copolymer, the binder in the negative electrode slurry is wrapped around the surface of the graphite material to form a positive charge layer, and the mutual repulsion makes the slurry stably suspended, which greatly improves the dispersibility of the graphite material and enhances the stability of the slurry. If the cationic unit content is too low, it cannot effectively participate in the polymerization reaction and cannot meet the effect of better dispersing graphite; if the cationic unit content is too high, it cannot fully participate in the polymerization, resulting in side reactions between the monomer residue and the electrolyte, reducing the battery cycle life.

[0027] In some embodiments, the mass ratio of the acrylic acid ester unit to the cationic unit is (30-70): (5-30). By controlling the content of the cationic unit, the amount of positive charge in the binder is adjusted to improve dispersibility.

[0028] Specifically, the mass ratio of the acrylate unit to the cationic unit includes, but is not limited to, 30:30, 70:5, 40:15 or 50:30.

[0029] In a preferred embodiment, the mass ratio of the acrylic acid ester unit to the cationic unit is (40-55):(8-15).

[0030] In some embodiments, the acrylic acid ester unit is a structural unit obtained by polymerization of acrylic acid ester monomers, and the acrylic acid ester monomers include one or more of methyl acrylate, ethyl acrylate, isobutyl acrylate, tert-butyl acrylate, butyl acrylate, 2-isooctyl acrylate, lauryl acrylate, octadecyl acrylate, methyl methacrylate, butyl methacrylate, phenyl methacrylate, and n-hexyl acrylate. By selecting the above acrylic acid ester monomers, the negative electrode binder has an appropriate electrolyte swelling degree.

[0031] In some embodiments, the vinyl aromatic unit is a structural unit obtained by polymerization of a vinyl aromatic monomer, and the vinyl aromatic monomer includes one or more of styrene, β-methylstyrene, 4-methoxystyrene, and 2-methylstyrene. By selecting the above vinyl aromatic monomers, the negative electrode binder has an appropriate glass transition temperature, thereby improving the cracking problem during the electrode processing.

[0032] In some embodiments, the acrylamide unit is a structural unit obtained by polymerization of acrylamide monomers, and the acrylamide monomers include one or more of hydroxyethyl acrylamide, isobutyloxymethyl acrylamide and diacetone acrylamide. The above acrylamide monomers are selected to further increase the bonding strength between the negative electrode binder and the active material and the current collector foil.

[0033] In some embodiments, the acrylate-polyol unit is a structural unit obtained by polymerization of acrylate-polyol monomers, and the acrylate-polyol monomers include one or more of poly(ethylene glycol) diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, and poly(propylene glycol) dimethacrylate.

[0034] The cross-linking unit is a structural unit obtained by polymerization with the participation of a cross-linking agent, and the cross-linking agent includes one or more of diethylene glycol dimethacrylate, ethylene glycol diacrylate, tetraethylene glycol diacrylate, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, neopentyl glycol diacrylate, 1,6-hexanediol dimethacrylate, and pentaerythritol tetraacrylate. By selecting the above-mentioned acrylate-polyol monomers and cross-linking agents, the negative electrode binder has a cross-linked network structure to control its swelling degree and rebound. If the proportion of the cross-linking agent is too low, the effect of controlling the swelling degree and inhibiting the rebound of the binder itself cannot be achieved. If the proportion is too high, the cross-linking agent is easy to remain and react with the electrolyte to deteriorate the battery performance.

[0035] Specifically, the preparation method of the negative electrode binder comprises the following steps: The polymeric emulsifier, the cationic emulsifier, the crosslinking agent and water are mixed, and then mixed with acrylate monomers, vinyl aromatic monomers, acrylamide monomers, acrylate-polyol monomers and cationic monomers to obtain a pre-emulsion.

[0036] Water, a buffer, an initiator and a pre-emulsion are mixed and reacted at a temperature of 40 to 80° C. for 1 to 10 hours to obtain a cationic binder emulsion.

[0037] The mass ratio of the polymeric emulsifier to the copolymer is (0.1-1.0):(40-60).

[0038] The mass ratio of acrylic acid ester monomer, cationic emulsifier, buffer and initiator is (30-70): (0.01-0.2): (0.01-10): (0.1-1.5).

[0039] In the present invention, the polymeric emulsifier, cationic emulsifier, buffer, and initiator are not particularly limited, and various substances commonly used in the field of chemical synthesis can be used.

[0040] Specifically, the cationic emulsifier includes one or more of dodecyl ammonium chloride, hexadecyl trimethyl ammonium chloride, octadecyl trimethyl ammonium chloride, hexadecyl trimethyl ammonium bromide, hexadecyl pyridinium bromide, and octadecylamine polyoxyethylene ether diquaternary ammonium salt.

[0041] The polymeric emulsifier includes one or more of allyl polyoxyethylene ether, allyl polyoxyethylene ether sulfonic acid ammonium salt, allyl-containing ether sulfonic acid sodium salt, sodium vinyl sulfonate, and double-bond alkyl polyoxyethylene phosphate.

[0042] The buffer includes one or more of sodium bicarbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and hydroxyethylaminodiacetic acid. The initiator includes one or more of azobisisobutyronitrile, azobisisobutyramidine hydrochloride, azobisisopropylimidazoline hydrochloride, dimethyl azobisisobutyrate, ammonium persulfate, sodium persulfate, and potassium persulfate.

[0043] An embodiment of the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer is made of any of the negative electrode binders described above.

[0044] An embodiment of the present application provides a secondary battery, including a positive electrode sheet, an electrolyte, and the negative electrode sheet as described above.

[0045] The present invention is further described below by way of examples.

[0046] The negative electrode binder, negative electrode and secondary battery disclosed in the present invention are specifically described.

[0047] Example 1 Negative electrode binder 0.5 parts of polymeric emulsifier (allyl polyoxyethylene ether), 40 parts of acrylate monomer (methyl acrylate), 20 parts of vinyl aromatic monomer (styrene), 10 parts of cationic monomer (methacryloyloxyethyl dimethyl dodecyl ammonium bromide), 20 parts of acrylamide monomer (hydroxyethyl acrylamide), 15 parts of acrylate-polyol (poly (ethylene glycol) diacrylate), 1 part of crosslinking agent (tetra (ethylene glycol) diacrylate), 0.5 parts of initiator (azobisisobutyronitrile), 0.05 parts of cationic emulsifier (dodecyl ammonium chloride), 1 part of buffer (sodium bicarbonate), and 70 parts of water.

[0048] Mixing a polymeric emulsifier, a cationic emulsifier, and a crosslinking agent with water, and then mixing with an acrylate monomer, a vinyl aromatic monomer, an acrylamide monomer, an acrylate-polyol monomer, and a cationic monomer to obtain a pre-emulsion; Water, a buffer, an initiator and a pre-emulsion are mixed and reacted at a temperature of 80° C. for 5 hours to obtain a cationic binder emulsion having a solid content of 45%.

[0049] Negative plate 96% graphite, 1.5% thickener sodium carboxymethyl cellulose, and 1% conductive carbon black were stirred at a low speed of 15rpm for 15 minutes, water was added to adjust the solid content to 66%, and then pre-stirred at 40rpm for 15 minutes and kneaded. After stirring at 40rpm for 40 minutes, high-speed 15m / s was used for dispersion for 40 minutes, and 1.2% cationic binder was added. After dispersion at 5m / s for 20 minutes, vacuum defoaming was performed and the material was discharged. Then the negative electrode slurry was coated on both sides of the negative electrode current collector Cu foil, and the single-sided coating surface density was 120g / m 2 , dried, cold pressed (compacted density 1.7g / cm 3 ), slitting and other processes to obtain the negative electrode sheet.

[0050] Positive electrode The positive electrode active material lithium iron phosphate, conductive carbon black, and positive electrode binder are mixed in a mass ratio of 90:3:7, and NMP is added to prepare positive electrode slurry. The positive electrode slurry is coated on aluminum foil and dried to obtain a positive electrode sheet.

[0051] Secondary battery preparation The negative electrode sheet, separator (PE film), and positive electrode sheet are wound in sequence so that the separator is placed between the positive and negative electrodes to play an isolating role, and the electrode assembly is made. The electrode assembly is placed in an outer package, and commercially available electrolyte is injected and packaged. After that, a secondary battery is obtained through processes such as liquid injection, formation, and exhaust.

[0052] Embodiments 2 to 12 Most of the steps of Examples 2 to 12 are the same as those of Example 1, except that the formula in Table 1 is used.

[0053] Comparative Examples 1 to 5 Most of the steps of Comparative Examples 1 to 5 are the same as those of Example 1, except that the formulation in Table 1 is used.

[0054] Table 1

[0055] The binder, negative electrode slurry, negative electrode sheet, and secondary battery prepared in the above examples and comparative examples were subjected to the following tests.

[0056] 1) Electrolyte quality swelling test: At standard atmospheric pressure and 25°C, 1M lithium hexafluorophosphate is added to a mixed solution of ethylene carbonate and ethyl methyl carbonate in a mass ratio of 1:1 as an electrolyte. Take two containers and add the electrolyte, make the wetting agent into a thin film and dry and weigh it to obtain W initial. The film specification is a circular sheet with a diameter of 20 mm and a thickness of 20 μm. The wetting agent film is immersed in the electrolyte, and after 72 hours, it is taken out and the electrolyte on the surface is wiped dry and weighed to obtain W balance. The mass swelling degree = (W balance - W initial) / W initial * 100%.

[0057] 2) Negative electrode slurry viscosity stability test: After the negative electrode slurry is prepared, a rotor of model 3# is used to rotate at a speed of 12 rpm. The viscosity of the negative electrode slurry measured under this condition is the initial viscosity. The viscosity of the slurry is tested again after the slurry is left to stand for 24 hours.

[0058] 3) Pole rebound test: Roll the coated electrode to ensure a compaction density of 1.7 g / cm 3 The electrode thickness at this time of the test is the initial thickness. After the electrode is placed in a moisture-proof cabinet in a constant temperature room for 24 hours, the thickness measured with a micrometer is the cold-pressed thickness after 24 hours. The electrode rebound rate = (electrode thickness after 24 hours - initial thickness) / initial thickness × 100%. Take 10 points for each electrode and calculate the average of the 10 points.

[0059] 4) Negative electrode peel strength test: The coated single-sided negative electrode sheet was heated at 2.4 g / cm 3 After compaction, a tensile testing machine with a range of 20N was used. The electrode was cut into 20cm long and 3cm wide. 3M double-sided tape was attached to the steel plate. The electrode coating was fixed on the tape on the steel plate with the surface facing down. After rolling back and forth 6 times with a 2.5kg roller, the coating and copper foil were torn off. The upper plate clamped the copper foil side and stretched at a speed of 50mm / min and 180°C. The data of the stable tension section was recorded as the peel strength (N / m).

[0060] 5) Normal temperature cycle test The specific method is: after placing the battery in a constant temperature test room at 25℃±2℃ for 1h, charge it to 3.65V at 1C constant current and constant voltage, with a cut-off current of 0.05C; discharge it to 2.5V at 1C constant current, and record the discharge capacity; repeat the above steps 500 times, and calculate the capacity retention rate.

[0061] 6) Full charge rebound test of negative electrode: The cells that have been fully charged are fully charged at constant current and constant voltage at 0.5C, and the cells are placed in a dry room (relative humidity 0.5%) for full-charge disassembly. The thickness of the negative electrode sheet is immediately tested after disassembly. The full-charge rebound rate = (full-charge disassembled electrode sheet thickness - electrode sheet thickness 24h) / electrode sheet thickness 24h × 100%. Take 10 points on each electrode sheet and calculate the average value of the 10 points.

[0062] The above test results are shown in Table 2 below.

[0063] Table 2

[0064] From the above results we can conclude that: By comparing Examples 1, 2, 11 and 12, it can be seen that if there is no cationic unit to reduce the dispersion of graphite, the peeling strength will be reduced, the material will fall off slightly when the full charge is disassembled, and the battery cycle life will be reduced; when the cationic unit content is on a downward trend and the content is lower than the scope of the present application, it will not be able to effectively participate in the polymerization reaction, and the effect of dispersing graphite cannot be achieved, resulting in poor 24h viscosity stability, low electrode peeling strength, high full charge rebound, and reduced battery cycle life; when the cationic unit content is on an increasing trend, although the graphite dispersion is good and the peeling strength is high, there are cationic monomer residues that cannot fully participate in the polymerization, which will inevitably react with the electrolyte and reduce the battery cycle life.

[0065] By comparing Examples 1, 3, and 4 with Comparative Example 1, it can be seen that when the proportion of acrylate units tends to decrease, the mass swelling degree is low, which is not conducive to the deintercalation of lithium ions during the charge and discharge process, affecting the cycle life of the battery; and the low peeling strength of the electrode piece leads to material shedding when fully charged, and the battery cycle life is reduced; and when the proportion of acrylate units tends to increase, although the peeling strength of the electrode piece can be guaranteed to a certain extent, the mass swelling degree of the binder is large, resulting in a large rebound at full charge, and local shedding of active materials in the later stage of the battery cycle, affecting the cycle life of the battery cell; when there are no acrylate units, the mass swelling degree of the binder is low, and the electrode piece peeling strength is low, resulting in a decrease in the battery cycle life.

[0066] By comparing Examples 1, 5, and 6 with Comparative Example 2, it can be seen that when the content of vinyl aromatic units is on an increasing trend, the swelling is small, which is not conducive to lithium ion deintercalation; when the content of vinyl aromatic units is on a decreasing trend, the hard monomer component is small, resulting in large swelling of the binder, large rebound of the pole piece and full charge rebound, and a decrease in the battery cycle life; if no vinyl aromatic units are included, the binder mass swelling degree is greater, resulting in an unstable binder structure, a large rebound of the pole piece, and a large swelling degree resulting in a large rebound of the battery at full charge, thereby reducing the battery cycle life.

[0067] By comparing Examples 1, 7, 8 and Comparative Example 3, it can be seen that: when the proportion of acrylamide units tends to increase, although the bonding force is high, the glass transition temperature of the binder will increase, making the electrode hard and brittle and not conducive to processing; when the proportion tends to decrease, the bonding force between the active substance and the foil will be reduced, resulting in a high rebound of the electrode when fully charged and a decreased battery cycle life; when no acrylamide units are added, the electrode peeling strength is low, and a large area of ​​material is lost when fully charged, thereby reducing the battery cycle life.

[0068] By comparing Examples 1, 9, 10 and Comparative Example 4, it can be seen that: when the proportion of acrylate-polyol units tends to decrease, the swelling degree of the binder will be reduced, which is not conducive to the deintercalation of lithium ions during the charge and discharge process, and the lower peel strength will affect the battery cycle life; when the proportion tends to increase, the swelling degree of the binder will increase, resulting in increased full-charge rebound and decreased battery cell cycle life; when the acrylate-polyol units are not added, the mass swelling degree and peel strength of the binder are both low, which reduces the battery cycle life.

[0069] By comparing Example 1 with Comparative Example 5, it can be seen that the 24h viscosity stability, pole piece rebound, peel strength, full charge rebound and cycle life of the conventional SBR system are far inferior to those of the binder of the present invention.

[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A negative electrode binder, characterized in that: The negative electrode binder comprises a copolymer, and the copolymer comprises an acrylate unit, a vinyl aromatic unit, an acrylamide unit, an acrylate-polyol unit and a crosslinking unit.

2. The negative electrode binder according to claim 1, characterized in that The mass ratio of the acrylic acid ester units, vinyl aromatic units, acrylamide units, acrylic acid ester-polyol units and cross-linked structural units is (30-70): (10-50): (5-30): (8-25): (0.5-2).

3. The negative electrode binder according to claim 1, characterized in that The copolymer also includes a cationic unit, which is a structural unit obtained by polymerization of a cationic monomer containing a double bond, and the cationic monomer includes one or more of methacryloyloxyethyl dimethyl dodecyl ammonium bromide, methacryloyloxyethyl dimethyl hexadecyl ammonium bromide, methacryloyloxyethyl trimethyl ammonium bromide, methacryloyloxyethyl dimethyl butyl ammonium bromide, methacryloyloxyethyl dimethyl pentyl ammonium bromide, methacryloyloxyethyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium chloride and dimethyl diallyl ammonium chloride.

4. The negative electrode binder according to claim 3, characterized in that The mass ratio of the acrylic acid ester unit to the cationic unit is (30-70):(5-30).

5. The negative electrode binder according to claim 1, characterized in that The acrylic acid ester unit is a structural unit obtained by polymerization of acrylic acid ester monomers, and the acrylic acid ester monomers include one or more of methyl acrylate, ethyl acrylate, isobutyl acrylate, tert-butyl acrylate, butyl acrylate, 2-isooctyl acrylate, lauryl acrylate, octadecyl acrylate, methyl methacrylate, butyl methacrylate, phenyl methacrylate, and n-hexyl acrylate.

6. The negative electrode binder according to claim 1, characterized in that The vinyl aromatic unit is a structural unit obtained by polymerization of a vinyl aromatic monomer, and the vinyl aromatic monomer includes one or more of styrene, β-methylstyrene, 4-methoxystyrene, and 2-methylstyrene.

7. The negative electrode binder according to claim 1, characterized in that The acrylamide units are structural units obtained by polymerization of acrylamide monomers, and the acrylamide monomers include one or more of hydroxyethyl acrylamide, isobutoxymethyl acrylamide and diacetone acrylamide.

8. The negative electrode binder according to claim 1, characterized in that The acrylate-polyol unit is a structural unit obtained by polymerization of acrylate-polyol monomers, and the acrylate-polyol monomers include one or more of poly(ethylene glycol) diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, and poly(propylene glycol) dimethacrylate; And / or, the cross-linking unit is a structural unit obtained by polymerization involving a cross-linking agent, and the cross-linking agent includes one or more of diethylene glycol dimethacrylate, ethylene glycol diacrylate, tetra(ethylene glycol) diacrylate, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol diacrylate, 1,6-hexanediol dimethacrylate, and pentaerythritol tetraacrylate.

9. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode binder according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: It comprises a positive electrode sheet, an electrolyte and the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Binder for a secondary battery having superior adhesive force

    CN102770995A

  • Binder composition for storage device, slurry for storage device, electrode for storage device, separator, and storage device

    CN105378989A

  • Water-based polymer binder as well as preparation method and application thereof

    CN117511459A

  • Negative electrode binder, negative electrode plate and lithium ion battery

    CN118406455A

Cited By

  • Negative electrode plate and lithium ion battery thereof

    CN120280483A

  • Binder, negative plate and lithium ion battery

    CN120329889A

  • A binder, a negative electrode sheet, and a lithium ion battery

    CN120329889B

  • Binder, negative electrode slurry, negative electrode plate and battery

    CN120442187A

  • A binder, a negative electrode slurry, a negative electrode sheet, a battery

    CN120442187B